Fluid mechanics hydraulic mechinery and advanced hydraulics - Manohar, M (Vikas Publishing House, 1999)
Fluid mechanics hydraulic mechinery and advanced hydraulics / Manohar, M. -- New Delhi: Vikas Publishing House, 1999 532 M266e2 v2 No. of Copies : 1